Improved thermoelectric performance in PbSe–AgSbSe2 by manipulating the spin-orbit coupling effects. (December 2020) - Duan, Sichen; Wang, Hongxiang; Liu, Guo-Qiang; Wu, Qingsong; Man, Na; Zhang, Qiang; Tan, Xiaojian; Yin, Yinong; Xiao, Yukun; Hu, Haoyang; Xu, Jingtao; Guo, Kai; et al.
Abstract: The thermoelectric performance of a semiconductor is intrinsically limited by the coupling of the transport factors, originating in the mechanism of band gap opening. Here we report the anomalous semiconductor AgSbSe2 -alloyed PbSe, in which the spin-orbit coupling (SOC) induced band gap allows the decoupling of electrical conductivity and Seebeck coefficient. In such a SOC semiconductor, the decrease of lattice constant increases the band gap from 0.23 eV up to 0.5 eV, seemingly in contrast to the previously measured negative pressure coefficient of band gap. Very different thermoelectric behaviors from the pristine PbSe were observed in PbSe–AgSbSe2, and finally a high peak ZT of 1.65 at 858 K and a remarkable average ZT (300–858 K) of 0.86 were obtained. This study reveals the novel relativistic effects in PbSe–AgSbSe2 system, and its thermoelectric performance is believed to have a large potential to be further improved. Graphical abstract: Image 1 Highlights: By alloying with AgSbSe2, PbSe undergoes a transition from a band semiconductor to a SOC semiconductor. By tuning the spin-orbit coupling effect, Seebeck coefficient is significantly enlarged. A high ZT of 1.65 at 858 K and a remarkable average ZT of 0.86 were achieved in PbSe–AgSbSe2 . The determined small band effective mass for PbSe–AgSbSe2 promises the further improvement of thermoelectric performance.